2008
DOI: 10.1093/hmg/ddn184
|View full text |Cite
|
Sign up to set email alerts
|

A risk haplotype of STAT4 for systemic lupus erythematosus is over-expressed, correlates with anti-dsDNA and shows additive effects with two risk alleles of IRF5

Abstract: Systemic lupus erythematosus (SLE) is the prototype autoimmune disease where genes regulated by type I interferon (IFN) are over-expressed and contribute to the disease pathogenesis. Because signal transducer and activator of transcription 4 (STAT4) plays a key role in the type I IFN receptor signaling, we performed a candidate gene study of a comprehensive set of single nucleotide polymorphism (SNPs) in STAT4 in Swedish patients with SLE. We found that 10 out of 53 analyzed SNPs in STAT4 were associated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
167
0
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 182 publications
(181 citation statements)
references
References 48 publications
11
167
0
1
Order By: Relevance
“…Interestingly, higher ORs were reported in samples of European origin from patients with severe disease manifestations for this gene. 11,12 The higher OR found in our Asian populations compared to those in Caucasians on rs7574865 may be a reflection of the disease severity in Asians. Our data on the subphenotype stratification are largely consistent with the findings by Taylor et al, 11 which we believe, with increased sample size, may provide further evidence on the stronger association of rs7574865 with severe phenotypes of the disease, such as hematologic disorder, nephritis and ds-DNA antibody production.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Interestingly, higher ORs were reported in samples of European origin from patients with severe disease manifestations for this gene. 11,12 The higher OR found in our Asian populations compared to those in Caucasians on rs7574865 may be a reflection of the disease severity in Asians. Our data on the subphenotype stratification are largely consistent with the findings by Taylor et al, 11 which we believe, with increased sample size, may provide further evidence on the stronger association of rs7574865 with severe phenotypes of the disease, such as hematologic disorder, nephritis and ds-DNA antibody production.…”
Section: Discussionmentioning
confidence: 88%
“…[8][9][10] SNP rs7574865 was found to be associated with lupus nephritis, ds-DNA antibody production and age of onset. 11,12 In the GWA study by Hom et al, 7 rs7574865 in STAT4 showed highly significant association with SLE risk, with a P-value only second to variants in the human leukocyte antigen locus. In addition to rs7574865, both Harley et al 8 and Hom et al 7 showed that rs7601754 was also significantly associated with SLE.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, gene polymorphisms at the interferon regulatory factor 5 (IRF5), a major mediator of TLR-triggered expression of type I IFN [53] and other proinflammatory cytokines, including TNFa [54], act additively with STAT4 genotype to increase the risk for SLE [13,55]. This fact could be explained by the functional link between both molecules, since the risk allele of STAT4 determines a higher frequency of anti-dsDNA antibodies in SLE patients, allowing a continued type I IFN stimulation of the STAT4-dependent autoimmune response [13,53].…”
Section: Discussionmentioning
confidence: 99%
“…This fact could be explained by the functional link between both molecules, since the risk allele of STAT4 determines a higher frequency of anti-dsDNA antibodies in SLE patients, allowing a continued type I IFN stimulation of the STAT4-dependent autoimmune response [13,53].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation